Retro-Element Gypsy-163 Is Differentially Methylated in Reproductive Tissues of Apomictic and Sexual Plants of Cenchrus ciliaris - Rathore, Priyanka; Raina, Soom Nath; Kumar, Suresh; Bhat, Vishnu (Frontiers in Genetics, 2020)
Apomixis, an asexual mode of reproduction through seeds, has an immense scope for crop improvement due to its ability to fix hybrid vigour. In C. ciliaris, a predominantly apomictically reproducing range grass, apomixis is genetically controlled by an apospory-specific-genomic-region (ASGR) which is enriched with retrotransposons. Earlier studies showed insertional polymorphisms of a few ASGR-specific retrotransposons between apomictic and sexual plants of C. ciliaris. REs are mainly regulated at transcriptional level through cytosine methylation. In order to understand the possible association of ASGR-specific retrotransposon to apomixis, extent and pattern of differential methylation of Gy163 RE and its impact on transcription was investigated in two genotypes each of apomictic and sexual plants of C. ciliaris. We observed that Gy163, encodes for an integrase domain of RE Ty3-gypsy, is differentially methylated between reproductive tissues of apomictic and sexual plants. However, leaf tissues did not exhibit differential methylation between apomictic and sexual plants. Among the three contexts (CG, CHG and CHH) of cytosine methylation, the maximum variation was observed in CHH context in reproductive (at aposporous initial and mature embryo sac stages) tissues of apomictic plants implicating RdDM pathway in methylation of Gy163. Quantitative PCR analysis showed that Gy163 transcripts are expressed more in the reproductive tissues of apomictic plants compared to that in the sexual plants, which was negatively correlated with the methylation level. Thus, the study helps in understanding the role of RE present in ASGR in epigenetic regulation of apomictic mode of reproduction in C. ciliaris.